A PRÁTICA DAS ROÇAS ENTRE OS TERENA DA ALDEIA IPEGUE: PERMANÊNCIAS E ATUALIZAÇÕES - ELZEBER PAIZ FLORES (2023)
This research aims to demonstrate the practice of swiddens carried out by the Terena residents of the Ipegue village, in the Taunay/Ipegue Indigenous Land, located in the municipality of Aquidauana-MS. In this sense, it privileged the discussions carried out by the works developed by indigenous researchers, a script of questions was also elaborated, which composed a questionnaire applied to twelve residents of the village. The answers to the questions were analyzed and constituted the main information of this research. Because it was through the information obtained from the indigenous farmers that this text was produced, since they allowed demonstrating that the work in the fields is still carried out by the Terena, both for subsistence agriculture, and to market their products in the village itself, as well as in neighboring villages and also in nearby towns. In this way, maintaining the practice of gardens among them.